Aplicação de bioestimulantes e espaçamento de plantio na produção e conservação pós-colheita de melão - Góes, Glêidson Bezerra de (Universidade Federal Rural do Semi-Árido, 2015)
The use of new technologies aimed at improving the quality of fruit is needed to meet consumer demands and this should remain for a longer time in order to reach distant consumer markets. Thus, this study evaluated the influence of the application of bio-stimulants and spacing of planting the melon postharvest conservation. For this, two experiments were conducted at the Farm Garden, located at Pau-Branco community in Mossoró-RN, to assess the influence of bio-stimulants, application forms and planting space in post-harvest melons conservation. The experiments were divided into two phases: the field and the laboratory. The first experiment evaluated the effect of bio-stimulants and application form in pre-harvest quality and melon postharvest conservation Yellow 'Iracema'. The field phase of this experiment was conducted in a randomized blocks in a factorial scheme with an additional treatment 2 x 2 + 1, two bio-stimulants (Crop Set® and Spray Dunger®), two application forms (sprayed and fertilized) and a control (without product application), with five repetitions. The second experiment evaluated the influence of spacing and biostimulant in the production, quality and melon conservation hybrid Frog Skin Sancho. For the field phase of this experiment, we adopted a randomized blocks in factorial 3 x 2, with three spacing between plants (40, 45 and 50 cm) and two applications of bio-stimulant Crop Set® (with and without), with four replications. In both experiments, the combination of factors constituted the plots where the fruits were sampled for characterization in the laboratory quality during storage. The fruit harvest was performed when they reached commercial maturity, and on this occasion we assessed the number of fruits per plant, number of fruits per meter, average fruit weight and productivity. The laboratory phase of both experiments was conducted in a completely randomized design with split plots in storage time with eight replications. At that stage, one fruit group was characterized, the day after the harvest, and the other were stored in refrigeration chamber regulated at 101ºC and 902% RH, time-lapse of 14, 21, 28 and 35 days. At each time interval, the fruit were evaluated by mass loss (ML), pulp firmness (PF), soluble solids (SS), titratable acidity (TA), reason soluble solids/titratable acidity (ratio), pH, vitamin C (VC) and soluble sugars. The data were submitted to analysis of variance and the significant variables were compared by the Tukey test, and the average of the control treatment compared using the Dunnett test and for the significant variables in the storage life regression analysis was performed. The biostimulants and the application form before the harvest influenced the quality and service life Yellow melon postharvest 'Iracema'. In Yellow melons, the application of bio-stimulant fertigation led to higher average fruit weight and productivity. The fruits of PF decreased during storage, the largest decrease occurred with the application of Spray Dunger® via spraying. The application by fertigation provided greater SS content in fruit, but during the storage period the SS content of the fruits decreased and remained at 35 days levels of 10%. The higher content of soluble sugars was found in the application form via fertigation by applying Crop Set®, but there were decreases of soluble sugar after 35 days of storage. There was a linear increase in VC content during storage. For the melon 'Piel de Sapo' production, quality and conservation of fruit were influenced by crop at different spacings and bio-stimulant. Production variables were not influenced by the application of Crop Set®. However, the number and the weight of commercial fruit per plant increased as increased spacing between plants. The storage of fruit provided an increase in melons ML with application of bio-stimulant, independently of planting space. PF fruit decreased during storage. The planting spacing of 40 cm provides lower SS of fruit than the spacings of 45 and 50 cm
Biostimulants application and spacing of planting in the production and melon postharvest conservation
Keywords: Cucumis melo L; Biostimulant; Planting spacing - melon; Farm Garden - Pau White / Mossoro-RN; Crop Set; Cucumis melo L; Bioestimulante; Espaçamento de plantio - melão; Fazenda Jardim - Pau Branco/Mossoró-RN; Crop Set; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA